2021
DOI: 10.1108/jec-07-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

Value creation through omnichannel practices for multi-actor customers: an evolutionary view

Abstract: Purpose The purpose of this paper is to investigate the omnichannel practices to porpose a conceptual overview to offer guidance on how to handle their inherent complexities. Design/methodology/approach This study is based on a literature review of more than 100 academics papers about the multichannel practices and omnichannel practices in the global market. Findings To this end, this paper identifies and addresses three limitations of the contemporary omnichannel literature: the failure to articulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 79 publications
0
9
0
1
Order By: Relevance
“…The rapid growth of technological advancement has led to the emergence of new channels that include retailers' websites, mobile apps, social networking sites, and kiosks, empowering consumers with more information and choices than ever before [24]. Growth in the number of online stores and changes seen in consumer behavior have compelled retailers to introduce multiple channels for interaction with customers [25]. Channels used by retailers are either digital (e.g., websites, mobile apps, social media) or physical stores that interact with consumers during their shopping journey [26].…”
Section: Omnichannel Retailing and Shopping Methodsmentioning
confidence: 99%
“…The rapid growth of technological advancement has led to the emergence of new channels that include retailers' websites, mobile apps, social networking sites, and kiosks, empowering consumers with more information and choices than ever before [24]. Growth in the number of online stores and changes seen in consumer behavior have compelled retailers to introduce multiple channels for interaction with customers [25]. Channels used by retailers are either digital (e.g., websites, mobile apps, social media) or physical stores that interact with consumers during their shopping journey [26].…”
Section: Omnichannel Retailing and Shopping Methodsmentioning
confidence: 99%
“…(Telli, 2020) identified the importance of omni-channel shopping services and value co-creation processes, whereby value co-creation is the mediating variable. It is also stated by (Costa Climent et al, 2022) that there are several sources of value cocreation that can be implemented by omni-channel. Based on the results of previous research, the second hypothesis that can be obtained is: H2: Omni-channel capability has a positive and significant effect on value co-creation…”
Section: The Effect Of Omni-channel Capability On Value Co-creationmentioning
confidence: 99%
“…(Telli, 2020) identified the importance of omnichannel shopping services and value co-creation processes. It is also stated by (Costa Climent et al, 2022) that there are several sources of value cocreation that can be implemented by omni-channel. This result is in accordance with the descriptive analysis of omni-channel capability variable, where customers have no hesitation in giving feedback and collaborating with the retailer in order to make ACE Hardware and the online channel better.…”
Section: Omni-channel Capability and Value Co-creationmentioning
confidence: 99%
“…Omni channel uniformity is also reflected when the retailer and deliverer of the orders are the same [31]. Costa et al [52] suggest that when the seller and deliverer of the orders are the same instead of third-party logistics provider consumer's perception of consistency is stimulated. Chen & Chi [38] in a study conducted in US on omni channel retailers found maintaining uniformity across omni channels greatly enhanced perceived behavioral control among US consumers.…”
Section: Omni Channel Uniformity and Perceived Behavioral Controlmentioning
confidence: 99%